THU0144 Understanding Fatigue in Patients with Rheumatoid Arthritis (RA): The Role of RA Disease Activity Flares. (9th June 2015) - Myasoedova, E.; Crowson, C.S.; Davis, J.M.; Matteson, E.L.; Gabriel, S.E.
Abstract : Background: Fatigue is a common problem in patients with rheumatoid arthritis (RA) which is highly endorsed by the RA patients. Flare represents an important aspect of RA disease experience with a crucial impact on patients' well-being. The impact of RA flares on fatigue in patients with RA is not fully understood. Objectives: We aimed to assess the association of RA flares, functional status, pain and well-being with fatigue perception in patients with RA using self-assessment questionnaires. Methods: Patients with RA (age≥18 yrs; 1987 ACR criteria) participating in an ongoing population-based cohort study completed flare-assessment in RA (FLARE) questionnaire and Bristol Rheumatoid Arthritis Fatigue (BRAF) questionnaire, as well as Health Assessment Questionnaire (HAQ) with visual analogue scale for pain (VAS pain) on 100mm scale during a study visit (2012-2014), and submitted a blood sample for C-reactive protein (CRP) and interleukin-6 (IL6) assessment. Retrospective medical records review was performed to collect physician clinical assessment (PCA) and patient global assessment (PGA) of RA disease activity on 100mm scale for the most recent clinical visit prior to the study visit. Pearson's correlation was used to examine relationships between the variables. Results: The study included 190 RA patients (mean age 63 years; 75% female; mean RA duration 13.6 yrs). The mean (standard deviation; SD) of the overall FLARE score was 2.52 (2.55) on 0-10 scale; 1.86 (2.45) for systemic subscale; 3.32 (3.09) for joint subscale. The mean (SD) of the overall BRAF score was 12.72 (13.55) on 0-70 scale; the subscale scores were as follows: physical fatigue 3.65 (4.43), living with fatigue 3.66 (4.45); cognitive fatigue 3.18 (3.21) and emotional fatigue 2.25 (2.64). Mean (SD) CRP was 4.15 (5.8) mg/L; IL6 3.48 (5.52) pg/ml; HAQ 0.66 (0.66); VAS pain 28.8 (24.8). BRAF score overall and all subscales were statistically significantly correlated with FLARE, HAQ, VAS pain, PGA and PCA (except for cognitive fatigue subscale which was only marginally associated with PCA, p=0.08; see Table ). There were no statistically significant associations of BRAF with CRP, IL6 or patient's gender. Younger age was statistically significantly associated with higher BRAF score overall, and in particularly with cognitive fatigue, but not with other BRAF subscales. Shorter RA duration was significantly associated with higher "living with fatigue" BRAF score. Conclusions: Flares of RA disease activity, as well as worsening functional status, pain, and overall well-being, but not inflammatory marker levels, are highly correlated with increased perception of fatigue. Our findings underscore the important role of RA flares in shaping the quality of life in patients with RA, and suggest an intricate relationship between self-perception of fatigue and flare, not reflected by inflammatory marker measures in patients with RA. Further studies are warranted to better understand the concept of RA flare and its impact on patient-reported outcomes. Disclosure of Interest: None declared